2003
DOI: 10.1159/000071963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex Steroid Hormones on the Expression of Somatostatin Receptors sst1 and sst5 in Goldfish Pituitary and Forebrain

Abstract: In the present paper the effects of estradiol and testosterone on the expression of the types 1 and 5 somatostatin receptors (sst1 and sst5) in the goldfish forebrain and pituitary were investigated. Estradiol increased the sst1 expression in both the forebrain and pituitary in a dose- and time-dependent manner. In addition, estradiol also increased the pituitary expression of sst5. On the other hand, testosterone had no effects on the expression of these receptor subtypes. Mature female goldfish were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The results, shown in Fig. 4, confirm that intraperitoneal administration of 50 ng/g body wt of ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) has no significant effect on PSS-I expression levels (Fig. 4A), whereas it inhibits the expression of PSS-II (Fig.…”
Section: Interaction Between Intraperitoneally Administered Ghrelin Asupporting
confidence: 56%
See 2 more Smart Citations
“…The results, shown in Fig. 4, confirm that intraperitoneal administration of 50 ng/g body wt of ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) has no significant effect on PSS-I expression levels (Fig. 4A), whereas it inhibits the expression of PSS-II (Fig.…”
Section: Interaction Between Intraperitoneally Administered Ghrelin Asupporting
confidence: 56%
“…It was recently shown that estradiol treatment reduces the in vitro GH responsiveness to SRIF-14 and simultaneously reduces the expression levels of sst2 in goldfish pituitary (12). However, estradiol treatment increases the expression levels of sst5 (9). Thus it seems that sst5 may be specialized in the transduction of gSRIF-28 actions in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, SSTRs represent a target for PC therapies, although the mechanism of their action as well as their cross talk with steroid receptors is still unclear. Estrogens up-regulate SSTR expression in BC cells as well as in goldfish pituitary and cerebral tissues (Djordjijevic et al, 1998; Kimura et al, 2001; Canosa et al, 2003). However, the effect of the combined treatment of SST analogs and estradiol on proliferation, EMT and migration of normal and PC cells has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in goldfish, rainbow trout, and mammals reported the effects of other hormones, including 17␤-estradiol, glucocorticoids, SS, and GH-releasing hormone (GHRH) on SSTR expression (4,16,19,21,22,31). For example, in rainbow trout, in vivo INS treatment reduced SSTR1B expression in the optic tectum, increased SSTR2 expression in the pancreas, and increased SSTR1B and SSTR2 expression in the liver (31).…”
Section: Discussionmentioning
confidence: 99%